Pengembangan Modul Pembelajaran Matematika Berbasis Etnomatematika (Tradisi Budaya Bugis) - Husnul Khatimah; Sitti Mania; Ahmad Farham Majid; Nur Yuliany (Department of Mathematics Education, 2022)
The purpose of this study was to determine the process of developing ethnomathematics-based teaching materials. The reference to the ADDIE development model which consists of several phases namely Analysis, Design, Development, Implementation, and Evaluation. . The product being developed is in the form of teaching materials, namely modules based on ethnomathematics (Bugis cultural tradition) on flat sided geometric material which was tested on 17 class VIII students of Pangkep Negeri MTs. The instruments used in this study were expert validation sheets, student activity observation sheets, teacher activity observation sheets in the implementation of learning, student response questionnaires, teacher response questionnaires, and learning achievement tests. The limited trial carried out, an ethnomathematics (Bugis cultural tradition) based module on flat sided geometric material in class VIII MTsN Pangkep has met the criteria of validity, practicality and effectiveness.